Bacterial contamination of ultrasound probes and coupling gels in a university hospital in Turkey - Kıran, Hakan; Aral, Murat; Kıran, Gürkan; Serin, Salih; Arıkan, Deniz Cemgil; Erkayıran, Uğurkan; Ekerbiçer, Hasan Çetin (The European Research Journal, 2019)
Objectives: Nosocomial outbreaks of infection originating from ultrasound probes and contaminated coupling gels have been reported. It was reported that the ultrasound probe, if cultured after routine scanning of intact skin, may become colonized with skin flora. Methods: Culture swabs from 22 probes of the 9 ultrasound machines and from the gels in the 10 gel folders were taken. All swabs taken from probe head, probe holder and the coupling gel in the folder at the beginning of the day were cultured. After fifth scanning and after wiping off the gel with a dry, nonsterile paper towel, cultures were again obtained from probe head and probe holder. Results: A total of 98 culture results were included of which 42.8% were positive for bacterial growth. The rate of bacterial contamination from probes at morning before the start of examination and after scanning were 34.1% and 56.8%, respectively and this difference was statistically significant (p = 0.023). Conclusions: We think that using nonsterile, dry, soft and absorbent paper towel after each procedure, could be inadequate for disinfection of probe head. Especially, good hand hygiene could decrease the rate of growth of bacterial colony at probe handle.